STRESS: um diagnóstico dos policiais militares da cidade de Natal Brasil - Costa, Marcos Aurélio de Albuquerque (2007)
Objectives: The purpose of the current study was to diagnose military police officers in Natal, Brazil as to the level and phase of stress in which they find themselves and the prevalent symptomatology (physical or mental). Methodology: Descriptive, crosscut study that investigated a sample of 264 individuals taken from a population of 3,193 military police officers of the Capital Police Command (CPC) in Natal, Brazil. The data were collected using the Lipp Stress Symptoms for Adults Inventory LSSI, and analyzed by tabulations, percentage calculations, t-test for proportions and Pearson s chi-squared test for associations between stress, symptomatology and military rank. Data collection was between June/2004 and January/2005. Results: It was found that 52.6% of the officers had symptoms of stress and 47.4% symptomatology of stress. This was distributed across all ranks, especially mid and upper-level officers as well as corporals and privates, with predominance in the resistance phase (36%) and a prevalence of psychological symptoms (76%). The only variable investigated that was related to stress was gender (P = 0.0337). Conclusions: It was concluded that there is stress among all ranks of military police officers in Natal, Brazil, especially mid and upper-level officers, corporals and privates, with a prevalence of psychological symptoms, low levels of physical symptoms and predominance in the resistance phase. It seems that stress levels do not differ significantly from those found in Brazilian men and women and do not indicate a situation of chronic fatigue